2021
DOI: 10.23917/pharmacon.v18i2.16861
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Penggunaan Antibiotik pada Pasien Meningitis dan Ensefalitis Bakteri di Bangsal Rawat Inap Rumah Sakit Rujukan Utama

Abstract: Inadequate antibiotic therapy for meningitis and bacterial encephalitis is one of the factors that can jeopardize patient safety and turn into a public health issue in a number of nations, including Indonesia. This phenomena has the potential to raise health-care expenses, which should be avoided in the era of the JKN program's implementation. The goal of this research was to describe the profile of antibiotic use and cost in hospitalized meningitis and bacterial encephalitis patients. This cross-sectional obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Data from the Republic of Indonesia Ministry of Health in 2015 showed that at the end of 2010, the number of meningitis cases that occurred in Indonesian society based on male sex was 12,010 clients (62.3%), while there were 7,371 women (38.7%). Of these cases, 1,025 (5.3%) sufferers of meningitis died (Rossetyowati et al, 2021). From health data for the province of West Java in 2014, the number of cases of meningitis was reported at around 0.7% (Nurliawati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Republic of Indonesia Ministry of Health in 2015 showed that at the end of 2010, the number of meningitis cases that occurred in Indonesian society based on male sex was 12,010 clients (62.3%), while there were 7,371 women (38.7%). Of these cases, 1,025 (5.3%) sufferers of meningitis died (Rossetyowati et al, 2021). From health data for the province of West Java in 2014, the number of cases of meningitis was reported at around 0.7% (Nurliawati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas non-pharmacological therapy is carried out by careful monitoring of vital signs because breathing is usually a Cheyne-Stokes pattern, giving intravenous fluids according to indications, lowering body temperature with warm compresses, administering oxygen, and positioning the head up 30o to improve oxygen circulation to the brain so that help raise awareness (Rossetyowati et al, 2021). The 30o head-up position technique or lying with the head 30 degrees is a simple and effective non-pharmacological therapy for increasing oxygen to the brain, increasing awareness and increasing cerebral tissue perfusion in patients with meningitis (Wahidin, Ngabdi Supraptini, 2020).…”
Section: Introductionmentioning
confidence: 99%